AUHIP CommuniquÉ: Meeting of the Minister of Defence, Government of Sudan, and Minister of SPLA Affairs, Government of Southern Sudan (Tufts Archival Research Center, 2005)
This is a communique by the African Union stating that Sudan's Minister of Defense, and Southern Sudan Minister of SPLA Affairs, met in Juba and endorsed an agreement about the Security Cluster on post-referendum arrangements.